Cultures of Anyone Studies on Cultural Democratization in the Spanish Neoliberal Crisis - Moreno-Caballud, Luis (Contemporary Hispanic and Lusophone Cultures, 2015)
The text of Cultures of Anyone is freely available online at the Modern Languages Open platform www.modernlanguagesopen.org Cultures of Anyone studies the emergence of collaborative and non-hierarchical cultures in the context of the Spanish economic crisis of 2008. It explains how peer-to-peer social networks that have arisen online and through social movements such as the Indignados have challenged a longstanding cultural tradition of intellectual elitism and capitalist technocracy in Spain. From the establishment of a technocratic and consumerist culture during the second part of the Franco dictatorship to the transition to neoliberalism that accompanied the 'transition to democracy', intellectuals and 'experts' have legitimized contemporary Spanish history as a series of unavoidable steps in a process of 'modernization'. But when unemployment skyrocketed and a growing number of people began to feel that the consequences of this Spanish 'modernization' had increasingly led to precariousness, this paradigm collapsed. In the wake of Spain's financial meltdown of 2008, new 'cultures of anyone' have emerged around the idea that the people affected by or involved in a situation should be the ones to participate in changing it. Growing through grassroots social movements, digital networks, and spaces traditionally reserved for 'high culture' and institutional politics, these cultures promote processes of empowerment and collaborative learning that allow the development of the abilities and knowledge base of 'anyone', regardless of their economic status or institutional affiliations.